miR-383 regulates sheep granular cell proliferation and apoptosis by targeting Bcl-2 - B. Zhang; S. Sun; W. Jia; J. Yang; X. Dou; Y. Wang; Y. Wang (Archives Animal Breeding)
During the reproductive process in female mammals, approximately 99 % of the follicles involved in egg development undergo atresia and are not utilised. The primary cause of follicular atresia is granulosa cell (GC) apoptosis. MicroRNAs (miRNAs) play an important regulatory role in follicular atresia. It has been widely confirmed that miR-383 is involved in the regulation of follicular GC proliferation, apoptosis, and steroid hormone secretion; however, its regulatory effect on sheep ovarian follicles remains unknown. In this study, we examined the regulatory role of miR-383 in ovine ovarian GC proliferation and apoptosis. We reveal that miR-383 overexpression induces cell death, inhibits cell proliferation, and causes a G1-phase cell cycle arrest. Based on prediction analysis of its target genes, miR-383 potentially targets the anti-apoptotic gene, Bcl-2. A subsequent dual-luciferase reporter assay confirmed this prediction. Overall, the results indicated that miR-383 regulates sheep GC proliferation and apoptosis by targeting Bcl-2. This study provides further insights into the regulatory role of miRNAs in ovine follicular development and atresia.